2015
DOI: 10.1002/cbin.10475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen and glucose deprivation on VEGF and its receptors in microvascular endothelial cells co‐cultured with mast cells

Abstract: The aim of this study was to determine the correlation between angiogenesis and the differential expression of vascular endothelial growth factor (VEGF) and its receptors in myocardial microvascular endothelial cells (MMVECs) co-cultured with mast cells (MCs) or mast cell granules (MCGs) under oxygen and glucose deprivation (OGD). MMVECs and MCs were isolated from Wistar rats. MCs spontaneously degranulated in OGD. The expression of VEGF peaked at 8 h and decreased from 16 h in OGD. However, the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recent research found that mast cells modulate VEGF levels under hypoxic conditions. A study revealed that the expression of VEGF, Flt-1, and Flk-1 increased significantly when myocardial microvascular endothelial cells were cocultured with mast cell granules or active mast cells [98]. It is interesting that mast cells are a source of VEGF secretion.…”
Section: Activated Systemic Inflammation Is Critical For the Progressmentioning
confidence: 99%
“…Recent research found that mast cells modulate VEGF levels under hypoxic conditions. A study revealed that the expression of VEGF, Flt-1, and Flk-1 increased significantly when myocardial microvascular endothelial cells were cocultured with mast cell granules or active mast cells [98]. It is interesting that mast cells are a source of VEGF secretion.…”
Section: Activated Systemic Inflammation Is Critical For the Progressmentioning
confidence: 99%